Badi in the Poetry of Ibn Al-Naqib Al-Husayni (1081 A. H) (Journal of the College of Basic Education, 2022)
This research deals with Kind of rhetorical popularized in the poetry of later times, namely (Badee) has chosen poetry of Ibn al-Naqeeb al-Husseini, which impressed us with his outstanding poetics and his keenness on the eloquent style that the Arabic poem in its previous era was characterized by. Verbal lexicality, and other virtuous moral methods.